2018
DOI: 10.1038/s41467-018-02984-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a consistent modeling framework to assess multi-sectoral climate impacts

Abstract: Efforts to estimate the physical and economic impacts of future climate change face substantial challenges. To enrich the currently popular approaches to impact analysis—which involve evaluation of a damage function or multi-model comparisons based on a limited number of standardized scenarios—we propose integrating a geospatially resolved physical representation of impacts into a coupled human-Earth system modeling framework. Large internationally coordinated exercises cannot easily respond to new policy targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 85 publications
1
46
0
Order By: Relevance
“…In contrast, Hartley et al (2017) found a difference in gross primary productivity due to differences in the distribution of plant functional types of between −12.7% and +11.2%. This is similar in magnitude to the feedbacks on land productivity found in Thornton et al (2017), but much smaller than the feedbacks from Monier et al (2018) or Reilly et al (2007).…”
Section: Global Mean Temperature (Gmt)supporting
confidence: 64%
See 2 more Smart Citations
“…In contrast, Hartley et al (2017) found a difference in gross primary productivity due to differences in the distribution of plant functional types of between −12.7% and +11.2%. This is similar in magnitude to the feedbacks on land productivity found in Thornton et al (2017), but much smaller than the feedbacks from Monier et al (2018) or Reilly et al (2007).…”
Section: Global Mean Temperature (Gmt)supporting
confidence: 64%
“…The changes in climate provided by CNRM induced changes in agriculture and ecosystem productivity in IMAGE. IGSM (Monier et al 2013(Monier et al , 2015(Monier et al , 2018 system and information on terrestrial productivity and trace gases back to the human system. Jarvis et al (2012) incorporated feedbacks between temperature change and emissions, implemented through changes in the carbon intensity of energy.…”
Section: Summary Of Modeling Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…One important factor to consider is the locations of surplus food production and food demand, given projected climate change and demographic trends such as those of recent studies [10,38,40]. According to the results of this study, current net exporting countries whose TFP is favorably impacted by climate change up to 2030 are predominantly located in cooler temperate climatic zones, e.g., the United States and Canada.…”
Section: Discussionmentioning
confidence: 82%
“…Increases in wealth may also strengthen trade while appropriate trade policies may alleviate many of the predicted shortcomings that developing countries will experience [8]. Moreover, Monier et al (2018) [38] indicate that few theories attempt to directly translate the impacts of global mean temperature change to GDP. Yet, Chalise and Naranpanawa (2016) [39] reported that overall, the Nepalese economy was significantly and negatively impacted by climate change-induced agricultural productivity losses, and indicated an urgent need to mainstream adaptation and mitigation strategies based on the results of a country-specific CGE model.…”
Section: Discussionmentioning
confidence: 99%